(untitled) (Research, Society and Development, 2021)
Plants with therapeutic properties are used by man throughout the history of humanity in the treatment and cure of diseases. The present study is a systematic review of meta-analysis carried out by searching the databases: Lilacs, Google Scholar and Pubmed. The present work has as its general objective to carry out a systematic review analyzing the profile of medicinal plant medicine interaction with the drugs most used by elderly people with blood pressure and as specific objectives: describe the use of medicinal plants by the elderly; checking the use of medicinal plants in high blood pressure. In view of the study, it is evident that the elderly make use of medicinal plants in order to prevent or treat any disease. Even having empirical knowledge about their use, they consume through self-medication, believing in the power of prevention, treatment and cure of diseases.